Herpetological Diversity of La Llana: an Inventory of Amphibians and Reptiles between Chagres and Portobelo National Parks, Colón, Panama (Biocenosis, 2025)
The community of La Llana, located between Chagres and Portobelo National Parks in the Colon Province, Panama, harbors little- studied forests. This study aimed to conduct an inventory of amphibians and reptiles in the forests adjacent to La Llana during the years 2006, 2007, and 2008. Eight 3.5-km transects were established, and daytime surveys were carried out, recording species non-systematically through visual and auditory observations. A total of 22 amphibian species (8 families, 13 genera) and 16 reptile species (7 families, 16 genera) were documented. The absence of records from the family Hylidae is notable, it is attributed to the methodology focused on searching for mammal tracks and setting up camera traps, which did not include scheduled nocturnal surveys, except for auditory records from the camp during the 2008 expeditions. The most abundant species were Colostethus aff. pratti, Oxybelis brevirostris, and Bothrops asper. The presence of endemic and/or threatened species was also recorded, such as Atelopus limosus, Strabomantis bufoniformis, Hemiphractus panamensis, Micrurus clarki, and Lachesis stenophrys. Although subject to improvement through more intensive sampling - including additional habitats and systematic nocturnal surveys -, this inventory significantly contributes to the knowledge of the region’s herpetofauna and highlights the importance of these forests as biodiversity reservoirs.
Keywords: Atelopus; tropical rainforest; conservation category; Hemiphractus; Lachesis